Islamic Republic of Afghanistan : Request for a 42-Month Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2020)
The COVID-19 pandemic has inflicted a heavy economic and social toll, amplifying the challenges of the armed conflict and fragility. Activity contracted sharply, and new external and fiscal financing needs emerged since the approval of the Rapid Credit Facility disbursement. President Ghani and Mr. Abdullah resolved the contested 2019 presidential election in mid-May, and peace negotiations between the government and Taliban started in September. The authorities are seeking renewed support from the international community for Afghanistan's development and reforms. Donors remain committed but encourage reform implementation and combatting corruption. Aid is likely to decline in the medium term underscoring the need to advance to self-reliance.